ELECTRONIC PROCUREMENT SYSTEMS: ENTERPRISES BEHAVIOR MODEL WITH NON-PRICE INDICATORS - Medzhybovska , N.S. (The actual problems of regional economy development, 2017)
This paper deals with the modeling of enterprise behavior during the reverse auction. We studied the benefits and limitations of reverse auctions and rules for their functioning in Ukraine. During the experiments we proved that the initial price cannot be a single measure for the decision-making. In this case the trading strategy and non-price indicators become crucial. We used the method of agent-based modeling and considered the following parameters for each participant as the starting price, the minimum price, trading strategy, non-price parameters (in this case – payment delay and delivery period).